Factors related to adverse mental health condition of demented family caregivers: A study in West Bengal, India - Basu, Ipsita; Mukhopadhyay, Susmita (Anthropological Review, 2019)
Dementia caregiving is a unique and the caregivers faces extreme challenges which affect caregiver’s mental health adversely. Family caregiving towards elderly individuals with dementia is becoming widespread. The study aims to evaluate the mental health status of dementia family caregivers and some related factors that affect their mental health condition. Present cross sectional study includes a total of 134 family caregivers. Socio-demographic and caregiving related data were collected using pre-tested questionnaires. Standardized questionnaires were used to collect data on caregivers’ mental health traits (measured in terms of level of stress and anxiety), level of psychosocial distress, support they provided and the care recipient’s behavioural symptoms associated with dementia. Mean age of the caregivers was 61.64 years (SD 13.89) while the care recipients were above 70 years of age. Mean age of care recipients was 75.46±7.26 years. Alzheimer’s type of dementia was the most common type found among them. Higher level of stress and anxiety was prevalent among the caregivers. Level of education, being a spouse, psychological distress has strong relationship with caregivers’ mental health condition. Behavioural abnormalities of care recipients were also responsible for poor mental health conditions of caregivers. Family caregiving is becoming the most suitable option nowadays and it associated with caregivers’ psychological distress and other health issues. Present study also revealed distressed mental health conditions of caregivers. Since care recipients remain dependent mostly on their family caregivers, it is necessary that caregivers should be fit mentally as well as physically. Therefore, proper support and management is needed for caregivers in near future.